SINOPSIS Begonia LIAR DI SUMATERA BARAT - Deden Girmansyah (Research Center for Biology-Indonesian Institute of Sciences, 2017)
The diversity of wild Begonia in West Sumatra is not well understood, while the habitat of Begonia has continuedly decreased by human activity or natural disaster. Therefore, some species are seriously undert hreat. Examinations of Begonia spp. were carried out using herbarium specimens from Andalas University Herbarium (ANDA), Herbarium Bogoriense (BO) and some field works in West Sumatra were conducted. A total of 33 species of Begonia were collected and identified as species level and could be used for identied Begonia species from West Sumatra.